ANALISIS DAMPAK SUBSTITUSI GULA PASIR DENGAN GULA MERAH PADA KADAR ANTIOKSIDAN DAN STABILITAS MIKROBA DALAM MINUMAN TRADISIONAL - Tri Ashfiya Sya'bani; Sukardi (PPPM POLTESA, 2026)
This study aims to comprehensively analyze the impact of substituting granulated sugar with brown sugar on antioxidant levels and microbial stability in various types of traditional spice-based beverages, both fermented and non-fermented. Brown sugar is known to contain bioactive compounds such as polyphenols, flavonoids, and Maillard reaction products, which play an important role in increasing antioxidant activity and the functional potential of products. The research method used was a literature review, analyzing 15 scientific sources from national and international journals indexed by Sinta and Scopus published between 2017 and 2025. Data were obtained through searches on the Google Scholar, ScienceDirect, and SpringerLink databases using the keywords “brown sugar,” “granulated sugar,” “antioxidants,” and “traditional beverages.” A descriptive analysis was conducted on previous research results highlighting the effect of sugar type on the chemical, sensory, and microbiological quality of beverages. The results of the study show that substituting granulated sugar with brown sugar consistently increases the antioxidant content in various traditional beverages such as bir pletok, serbat, and instant powdered drinks, through the contribution of phenolic compounds and melanoidins produced during heating. However, microbial stability is influenced by process factors such as water content, pH, sanitation, and storage, so the use of brown sugar does not directly guarantee the microbiological safety of the product. Overall, substituting granulated sugar with brown sugar has the potential to increase the functional value and health benefits of traditional beverages without compromising sensory quality, provided that optimal processing control and hygiene are maintained to ensure product stability and safety.